Chitosan–Calcium Aluminate as a Cell-homing Scaffold: Its Bioactivity Testing in a Microphysiological Dental Pulp Platform - Bordini, Ester Alves Ferreira; Stuani, Vitor de Toledo; Correa, Lígia Espoliar; Cassiano, Fernanda Balestrero; Lovison, Marcella Fernandes; Leite, Maria Luisa; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP]; Soares, Diana Gabriela (SAGE Publications, 2024)
In vitro models of the dental pulp microenvironment have been proposed for the assessment of biomaterials, to minimise animal use in operative dentistry. In this study, a scaffold/3-D dental pulp cell culture interface was created in a microchip, under simulated dental pulp pressure, to evaluate the cell-homing potential of a chitosan (CH) scaffold functionalised with calcium aluminate (the ‘CHAlCa scaffold’). This microphysiological platform was cultured at a pressure of 15 cm H2O for up to 14 days; cell viability, migration and odontoblastic differentiation were then assessed. The CHAlCa scaffold exhibited intense chemotactic potential, causing cells to migrate from the 3-D culture to its surface, followed by infiltration into the macroporous structure of the scaffold. By contrast, the cells in the presence of the non-functionalised chitosan scaffold showed low cell migration and no cell infiltration. CHAlCa scaffold bioactivity was confirmed in dentin sialophosphoprotein-positive migrating cells, and odontoblastic markers were upregulated in 3-D culture. Finally, in situ mineralised matrix deposition by the cells was confirmed in an Alizarin Red-based assay, in which the CHAlCa and CH scaffolds were adapted to fit within dentin discs. More intense deposition of matrix was observed with the CHAlCa scaffold, as compared to the CH scaffold. In summary, we present an in vitro platform that provides a simple and reproducible model for selecting and developing innovative biomaterials through the assessment of their cell-homing potential. By using this platform, it was shown that the combination of calcium aluminate and chitosan has potential as an inductive biomaterial that can mediate dentin tissue regeneration during cell-homing therapies.
Keywords: cell culture; chitosan; dental pulp; in vitro assay; tissue engineering